1995
DOI: 10.1002/path.1711750407
|View full text |Cite
|
Sign up to set email alerts
|

Absence of overexpression of p53 protein by intestinal carcinoid tumours

Abstract: A recessive gene on chromosome 17 encodes a protein, known as p53, which normally acts to regulate the cell cycle, its mutation and overexpression being amongst the commonest genetic abnormalities in human malignant neoplasms. As detected by immunolabelling using the anti-p53 protein antibody D07, overexpression was absent from a series of 22 intestinal carcinoid tumours (ten ileal, nine appendiceal, and three colorectal), nine overtly malignant, but was readily demonstrable in five of five colorectal adenocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 9 publications
2
7
0
2
Order By: Relevance
“…A few studies have reported p53 protein overexpression or p53 gene mutation in intestinal carcinoid tumors [39, 40, 41]. Along with our results, p53 overexpression has been reported to be absent in carcinoid tumors smaller than 20 mm or with submucosal invasion [40, 41].…”
Section: Discussionsupporting
confidence: 75%
“…A few studies have reported p53 protein overexpression or p53 gene mutation in intestinal carcinoid tumors [39, 40, 41]. Along with our results, p53 overexpression has been reported to be absent in carcinoid tumors smaller than 20 mm or with submucosal invasion [40, 41].…”
Section: Discussionsupporting
confidence: 75%
“…This is corroborated by lack of allelic loss of 17p, the chromosomal location of the p53 gene in tumors associated with pseudomyxoma peritonei in a previous study (17). Similarly, appendiceal carcinoid tumors have infrequent p53 gene mutations (19,20).…”
Section: Discussionsupporting
confidence: 62%
“…Vortmeyer et al (25) found loss of heterozygosity of p53 in PDEC and colorectal adenocarcinoma but not in WDET. Other authors described the absence of p53 overexpression in WDETs (26,27). Because the immunohistochemical expression of p53 in colorectal tumor tissues is inconsistent, we preferred to evaluate the p53 mutational status by single-strand conformation polymorphism-PCR as described before (7).…”
Section: Discussionmentioning
confidence: 99%